1997
DOI: 10.1172/jci119177
|View full text |Cite
|
Sign up to set email alerts
|

The vascular effects of L-Arginine in humans. The role of endogenous insulin.

Abstract: This study aimed at evaluating whether increased availability of the natural precursor of nitric oxide, L -arginine, could influence systemic hemodynamic and rheologic parameters in humans and whether the effects of L -arginine are mediated by endogenous insulin. 10 healthy young subjects participated in the following studies: study I, infusion of L -arginine (1 g/min for 30 min); study II, infusion of L -arginine plus octreotide (25 g as i.v. bolus ϩ 0.5 g/min) to block endogenous insulin and glucagon secreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(111 citation statements)
references
References 34 publications
5
104
1
1
Order By: Relevance
“…This term has been used to refer to situations in which exogenous L-arginine concentrations apparently determine the level of NO production even when intracellular levels of L-arginine are available in excess. Data supporting other explanations for this paradox have been put forward by other investigators (17,21,36,39). For example, Giugliano et al (39) demonstrated that i.v.…”
Section: Translational Control Of Inos By Arginine Can Explain the Armentioning
confidence: 78%
“…This term has been used to refer to situations in which exogenous L-arginine concentrations apparently determine the level of NO production even when intracellular levels of L-arginine are available in excess. Data supporting other explanations for this paradox have been put forward by other investigators (17,21,36,39). For example, Giugliano et al (39) demonstrated that i.v.…”
Section: Translational Control Of Inos By Arginine Can Explain the Armentioning
confidence: 78%
“…Insulin has vasodilative and hypotensive effects (3)(4)(5)(6)(7)(8)(9). It has been reported that hypertension was improved by insulin treatment in patients with DM (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, there has been considerable interest in the involvement of L-arginine in the release of insulin through NO pathways (4 -7,23), which may explain the hemodynamic and vascular effects of insulin (8,9). The coupling of L-arginine, insulin, and glucose in a rhythmic way sheds new light on this complex interplay that might be significant in pathological states.…”
Section: Results -mentioning
confidence: 99%
“…One other putative mechanism is the formation of nitric oxide (NO) from Larginine by the action of NO synthase in pancreatic ␤-cells (4 -7). It has been reported that systemic infusion of Larginine induces vasodilation, inhibits platelet aggregation, and reduces blood viscosity and that these effects are mediated by NO release (8,9). Although there might be a dietary need for L-arginine, it is produced endogenously from the turnover of the urea cycle within the liver and via conversion of citrulline to arginine in the renal proximal tubule (10,11).…”
mentioning
confidence: 99%